A quantitative study on organisational commitment and communication satisfaction of professional staff at a master's institution in the United States. Issue 5 (3rd September 2017) - Bray, Nathaniel J.; Williams, Laine
ABSTRACT: This study examined communication satisfaction and organisational commitment for professional staff at an American Master's institution using two quantitative surveys: Downs and Hazen's Communication Satisfaction Questionnaire and Meyer and Allen's TCM Employee Commitment Survey. One hundred and sixty-eight full-time and part-time staff participated in this single-institution survey. Descriptive statistics, correlations and linear regression analysis were used. This study resulted in three overarching conclusions. First, a relationship exists between organisational commitment and communication satisfaction in an American higher education context. Second, communication climate can predict normative organisational commitment. Third, participants in this study had a high level of affective commitment.